Developing a remote region: Tourism as a tool for creating economic diversity in Nunatsiavut - Fugmann, Gerlis (Études/Inuit/Studies, 2012)
In the academic literature, tourism has long been discussed as a tool for the economic development of peripheral regions. This article examines the success of this tool using Nunatsiavut (Northern Labrador) as a case study. Although the region’s private sector strongly relies on resource industries as its main economic pillar, the Nunatsiavut Government has since 2006 increasingly promoted other sectors, like tourism, to diversify its economy and create a more sustainable future. The article is based on a research project on bottom-up economic development in Nunatsiavut and will explore the early stages of the tourism industry, its challenges, and the employment and income opportunities it creates. Although currently only playing a minor role in the local economy, the efforts made by Tourism Nunatsiavut in this early phase have laid promising foundations that the region can build on in the future.